Development of GEBI: “game edukasi berbasis IoTs” for fashion students at vocational senior high school - Nasrillah, Yusrin; Yavie, Evania; Aini, Nurul; Krisnanda, Thiessa; Asfia, Yunita; Ubaidah, Siti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Research sought create and authenticate educational game GEBI (Game Edukasi Berbasis IoTs) targeted numeracy literacy enhancement in Pattern Making for Grade 10 students at SMKN 7 Malang studying Fashion Design and Production as part Phase E of Merdeka Curriculum. The game development followed the ADDIE model with validation as primary focus. The educational game GEBI developed through Liveworksheet platform which includes features such as login access, level-based contextual questions, multiple-choice tasks, instant feedback and progress tracking. This approach used constructivist pedagogy to develop essential numeracy skills including unit conversion and measurement interpretation to enable effective problem-solving for basic pattern drafting. Validation included participation from 30 students alongside two educational media experts and two subject matter experts. Questionnaire with 4-points Likert scale evaluated visual design together with pedagogy, content accuracy, examined interactivity and usability. Researchers applied quantitative analysis through percentage-based feasibility measures which required scores of 61% or higher. The feasibility study revealed GEBI's high feasibility after achieving total score of 93% which included 88% from media experts and 98% subject matter experts. The brief academic calendar created a limited development time which presented a major challenge. This research advances digital learning innovations in vocational education and recommends further studies evaluating success.